Analyzing Diguanylate Cyclase Activity In Vivo using a Heterologous Escherichia coli Host. Issue 1 (29th November 2018) - Fernandez, Nicolas; Waters, Christopher M.
Abstract: Bacterial biofilms are notorious for their deleterious effects on human health and industrial biofouling. Key processes in biofilm formation are regulated by the second messenger signal cyclic dimeric guanosine monophosphate (c‐di‐GMP); accumulation of c‐di‐GMP promotes biofilm formation, while lowering c‐di‐GMP promotes motility. Complex networks of modular enzymes are involved in regulating c‐di‐GMP homeostasis. Understanding how these enzymes function in bacterial cells can help enlighten how bacteria use environmental cues to modulate c‐di‐GMP and cell physiology. In this article, we describe a workflow that utilizes Escherichia coli as a heterologous host to allow the researcher to identify genes encoding potential c‐di‐GMP‐metabolizing proteins, to express the gene of interest from an inducible plasmid, and to directly detect changes in intracellular c‐di‐GMP using ultra‐performance liquid chromatography‐tandem mass spectrometry. © 2018 by John Wiley & Sons, Inc.